Analisis Frasa pada Teks Naratif dalam Buku Bahasa Indonesia Kelas VII SMP Kurikulum Merdeka - Endah Yustiani; Fairuzah Qolbi; Ninda Alifa; Widini Arti; Asep Purwo Yudi Utomo; Ahmad Ripai (Pusat Riset dan Inovasi Nasional, 2023)
Syntaxis analysis on narrative text in Indonesian language book class VII middleschool Merdeka curriculum focuses on analysis of phrases. The purpose of performing phrase analysis on this narrative text is to find, describe, and group into the types of phrases contained in narrative texts